The delicate task of linking industrial R&D to national competitiveness - Papadakis, Maria (Technovation)
The question posed in this research is whether US R&D-oriented competitiveness policies are likely to be effective in light of a number of concerns about the deterministic role R&D is presumed to play in competitiveness. Three releationships are explored : (1) R&D intensity and comparative advantage; (2) R&D intensity and competitive performance; and (3) US and Japanese relative R&D efforts and competitive performance. Although R&D was found to have a direct association with comparative advantage, it was not a systematic predictor of US industrial competitiveness. Relative to Japan, R&D was found to be a necessary but not a sufficient condition for competitive ability. Critical additional determinants are total factor productivity and levels of industrial basic research spending. The findings suggest that US R&D policies may enhance US technological innovation, but not necessarily the transformation of that skill into competitive strength.